2018
DOI: 10.4103/psychiatry.indianjpsychiatry_94_18
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities in acute coronary syndromes: Six-month follow-up study

Abstract: Introduction:Acute coronary syndrome (ACS) caused by coronary atherosclerosis include ST-segment elevation myocardial infarction (STEMI), non-STEMI, and unstable angina. The relation between psychiatric disorders and coronary artery disease is a complex one which includes the effect of the psychosocial factors on heart and vice versa. Point prevalence studies have been reported, but there is paucity of follow-up studies from India.Materials and Methods:The study is a follow-up evaluation at discharge of 248 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
(24 reference statements)
0
3
1
Order By: Relevance
“…The prevalence of depression in patients after ACS events is significantly increased compared to the general population because it has been shown that patients with ACS have a greater predisposition to present stressful events, as well as being more exposed to the threat of death and the loss of autonomy, which become stressors that generate depression. In this investigation, almost 8 out of 10 patients presented depression, which is consistent with what has been described in previous studies [24,25]. However, these results are higher than those described by Jayakumar et al [26], who found that 46.1% of patients with myocardial infarction presented depression.…”
Section: Mental Health Disorderssupporting
confidence: 93%
“…The prevalence of depression in patients after ACS events is significantly increased compared to the general population because it has been shown that patients with ACS have a greater predisposition to present stressful events, as well as being more exposed to the threat of death and the loss of autonomy, which become stressors that generate depression. In this investigation, almost 8 out of 10 patients presented depression, which is consistent with what has been described in previous studies [24,25]. However, these results are higher than those described by Jayakumar et al [26], who found that 46.1% of patients with myocardial infarction presented depression.…”
Section: Mental Health Disorderssupporting
confidence: 93%
“…Our ndings reveal that the most common anxiety disorder diagnosis was generalized anxiety disorder (11.5%) followed by panic disorder (8.3%) which is similar to a systematic review and meta-regression by Tully et al in 2014 (25). Likewise, another study from India in 2018 found panic disorder (12.10%) as the most common anxiety disorder in CAD patients followed by agoraphobia (2.40%) which is slightly different from our nding (11). Our ndings suggest that the majority of depressive disorders are mild in severity which is consistent with the nding by Altino et al,2017 and Yeshun et al 2019 who found that the majority of CAD patients had mild depression (26) (23).…”
Section: Discussioncontrasting
confidence: 64%
“…CAD patients with depression and anxiety co-morbidities are associated with worse cardiac outcomes (5). The prevalence rates of depression and anxiety varied among studies and ranged from 15-60% across the globe (6) , ( 7) , (8) , ( 9) , (10) , (11). Depressive symptoms are frequently masked by physical illness and manifest as severe somatic symptoms inconsistent with disease severity, making a diagnosis and intervention di cult for clinicians (4).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological and social elements both play important roles in the etiology, course, and outcome of CAD. A bidirectional relationship exists between cardiovascular diseases and psychiatric co-morbidities [10]. Depressive and anxiety disorders, anger, and post-traumatic stress are identifiable markers of psychological distress that have been significantly associated with CAD [11].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the risk of CAD and the severity of depression is direct, with reported increases of 1-2 times for minor depression and 3-5 times for major depression [15]. Anxiety has also been linked to negative illness outcomes [10]. The elevated risk posed by these psychological factors is comparable to more conventional CAD risk factors like smoking, dyslipidemia, and hypertension [16].…”
Section: Introductionmentioning
confidence: 99%